2020
DOI: 10.1080/08927022.2020.1859111
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative particle dynamics simulations of end-cross-linked nanogels

Abstract: Nanogels, due to their unique properties, have potential for promising applications in several fields. There is a growing interest in understanding which are the mechanisms controlling their properties, as those depend not only on composition, but also on internal structure. In this work Dissipative particle dynamics simulations were applied to simulate the formation of nanogels from monodisperse end-functionalized polymer chains, with the crosslinking reaction modelled using a distance-based algorithm, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been shown that within this simple scheme, the reaction parameters do not influence the final structure and properties [121]. The formation of end-crosslinked nanogels from isocyanate-functionalized prepolymers has been studied using DPD [122]. In this case, the linking reaction is not the urethane bond formation, but the cyclotrimerization itself, which is modeled as a two-step reaction, as it is shown in Figure 7A, with the formation of an intermediate active NCO dimer.…”
Section: Coarse-grained Modelsmentioning
confidence: 99%
“…It has been shown that within this simple scheme, the reaction parameters do not influence the final structure and properties [121]. The formation of end-crosslinked nanogels from isocyanate-functionalized prepolymers has been studied using DPD [122]. In this case, the linking reaction is not the urethane bond formation, but the cyclotrimerization itself, which is modeled as a two-step reaction, as it is shown in Figure 7A, with the formation of an intermediate active NCO dimer.…”
Section: Coarse-grained Modelsmentioning
confidence: 99%
“…In addition to conventional experimental approaches used to study nanogels directly in a laboratory where they are synthesised, nowadays we can also rely on computer simulations to study the properties of nanogels 6,[64][65][66][67][68][69][70][71][72][73][74] . Most of these works take as a basis a bead-spring model 75 to model polymer chains.…”
Section: Introductionmentioning
confidence: 99%